2023
DOI: 10.1051/itmconf/20235105001
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of Digital Platform Design

Abstract: Digital platforms disrupt today’s industries with novel offers and business models. Despite their revolutionizing impact, over 80% of platforms fail. To better understand what differentiates failing from successful platforms, we identified 30 platform success factors. These range from corporate value integration, where the platform strategy gets defined and the platform’s value definition, to the platform architecture covering all essential IT considerations and best practices making, e.g., innovation and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…[21], causalities behind failures of digital agriecosystems were investigated. In this regard, for step I.1 (data collection), learnings from the build-up and shutdown of NEVONEX, as well as publicly available information on failure causes of digital agriecosystems from [16,[22][23][24][25], were leveraged as input for this RCA. Next, a causal factor chart was created to organize and visualize events, conditions, and occurrences that led to failures of digital agriecosystems (step I.2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21], causalities behind failures of digital agriecosystems were investigated. In this regard, for step I.1 (data collection), learnings from the build-up and shutdown of NEVONEX, as well as publicly available information on failure causes of digital agriecosystems from [16,[22][23][24][25], were leveraged as input for this RCA. Next, a causal factor chart was created to organize and visualize events, conditions, and occurrences that led to failures of digital agriecosystems (step I.2).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ref. [23] identified thirty success factors for digital platforms and clustered them into three domains: corporate value integration, platform value, and platform architecture. In contrast, Cusumano et al focused on failure causes and showed that many digital platforms fail during their first years following market launch due to mispricing, lack of trust, poor competitor analysis, and/or late market entry [24].…”
Section: Causality Behind Failure Of Digital Agriecosystemsmentioning
confidence: 99%